Cardiorenal Syndrome is Present in Human Fetuses with Severe, Isolated Urinary Tract Malformations - Merz, Waltraut M. (Public Library of Science, 2013)
OBJECTIVE: We analyzed the association between renal and cardiovascular parameters in fetuses with isolated severe urinary tract malformations. METHODS: 39 fetuses at a mean gestational age of 23.6 weeks with nephropathies or urinary tract malformations and markedly impaired or absent renal function were prospectively examined. Fetal echocardiography was performed, and thicknesses of the interventricular septum, and left and right ventricular wall were measured. Blood flow velocity waveforms of the umbilical artery, middle cerebral artery, and ductus venosus were obtained by color Doppler ultrasound. Concentrations of circulating n-terminal pro-B-type natriuretic peptide (nt-proBNP), cystatin C, ß(2)-microglobulin, and hemoglobin were determined from fetal blood samples. RESULTS: Malformations included 21 cases of obstructive uropathy, 10 fetuses with bilateral nephropathy, and 8 cases of bilateral renal agenesis. Marked biventricular myocardial hypertrophy was present in all cases. The ratio between measured and gestational age-adjusted normal values was 2.01 (interventricular septum), 1.85, and 1.78 (right and left ventricular wall, respectively). Compared to controls, levels of circulating nt-proBNP were significantly increased (median (IQR) 5035 ng/L (5936 ng/L) vs. 1874 ng/L (1092 ng/L); p<0.001). Cystatin C and ß(2)-microglobulin concentrations were elevated as follows (mean ± SD) 1.85±0.391 mg/L and 8.44±2.423 mg/L, respectively (normal range 1.66±0.202 mg/L and 4.25±0.734 mg/L, respectively). No correlation was detected between cardiovascular parameters and urinary tract morphology and function. Despite increased levels of nt-proBNP cardiovascular function was preserved, with normal fetal Doppler indices in 90.2% of cases. CONCLUSION: Urinary tract malformations resulting in severe renal impairment are associated with biventricular myocardial hypertrophy and elevated concentrations of circulating nt-proBNP during fetal life. Cardiovascular findings do not correlate with kidney function or morphology.